The Effects of Boredom on EFL Learners' Engagement - Xie, Jin (Frontiers in Psychology, 2021)
This article aims to delve into the role of boredom on students’ engagement which has always attracted attention in that it is one of the most common academic feelings felt by students that causes them to feel more or less enthusiastic to engage in class activities, and there is a growing increase in such feelings among adolescents; therefore, its various dimensions are deserved to be taken into consideration. First and foremost, a variety of definitions from different points of view have been proposed. Then, with a focus on the distinction between state boredom and trait boredom which is one of the most radical classifications of boredom it has been continued. Following that, the antecedents of boredom are additionally taken into consideration along with the role of boredom in students’ engagement that necessitates a few changes in the curriculum of schools. Moreover, some coping strategies on how to overcome boredom have been featured. Finally, in the discussion part, the emphasis of the above-mentioned points in the learning context for both teachers and students has been discussed, and new suggestions for further studies have been proposed.